Analisis Pengeringan Kencur (Kaempferia galanga L.) Menggunakan Pengering Hybrid Tipe Rak dan Karakteristik Fisik Tepung Kencur yang Dihasilkan - Warji, Warji; Marreta, Rivania Pisca; Tamrin, Tamrin; Amien, Elhamida Rezkia (Jurnal Agricultural Biosystem Engineering, 2025)
Kencur (Kaempferia galanga L.) is an important ingredient in culinary and traditional medicine but has a limited shelf life due to its high moisture content. To overcome this, kencur can be processed into flour through drying. This study aims to analyze the effect of drying temperature on the drying time of kencur using three methods: sun drying, oven drying, and hybrid rack dryer, and to compare their efficiency based on drying duration, energy consumption, and drying capacity. The results show that the oven drying method requires the shortest drying time of 10 hours at 58°C with the highest energy consumption (1900 watts). The hybrid dryer takes 14 hours at 45°C with lower energy consumption (1300 watts) and a larger drying capacity. Sun drying takes the longest time, 20–22 hours at around 38°C, without electrical energy consumption. Although there are significant differences in drying time and efficiency, the physical characteristics of the resulting kencur flour show no significant differences between methods. Keywords: Kencur, Hybrid Dryer, Oven Drying, Sun Drying, Efficiency, Kencur Flour.